I suppose you meant x^2 + 3x + 2 = 0

we can factorize this guy. think of two numbers that when multiplied yields +2 and when added yields +3. +1 and +2 works, so:

x^2 + 3x + 2 = 0

=> (x + 2)(x + 1) = 0

=> x + 2 = 0 or x + 1 = 0 .........since if the product of two numbers give zero, one or the other number has to be zero

=> x = -2 or x = -1

these are the two roots. and the sum is .......?

alternate method:

for any quadratic y = ax^2 + bx + c

the sum of the roots is: -b/a

the product of the roots is: c/a